18F-FDG PET/CT Imaging of Bilateral Renal Metastasis of Breast Adenoid Cystic Carcinoma. (February 2016) - Hassoun, Hani; Alabed, Yazan Z.; Karls, Shawn; Probst, Stephan; Laufer, Jerome
Abstract : Abstract: We report the case of a 65-year-old woman with a history of adenoid cystic carcinoma (ACC) of the breast. Fifteen years after mastectomy, the patient underwent a right upper lobectomy for a lung mass, and biopsy indicated ACC metastasis. Ten years after lobectomy, an 18 F-FDG PET/CT was performed for restaging to rule out further metastases. We observed intense FDG uptake in enlarged polylobulated kidneys, which was biopsy proven as ACC metastasis.